Analisis Penyebab Keterlambatan Pengembalian Berkas Rekam Medis Rawat Jalan di Rumah Sakit Mitra Medika Bondowoso - Adlien Rizqo Fadillah; Novita Nuraini; Feby Erawantini; Ervina Rachmawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The delay in returning medical record file can affect medical record service and will hampered further activities, such as assembling, coding, analysis, or index activities. The return of outpatient medical records in Mitra Medika Bondowoso Hospital is still experiencing delays. In the first quarter of 2019 the total number of late outpatient medical records was 871 out of 7404 files or 11.76%. The purpose of the study was to analyze the causes of the delay in returning the outpatient medical record file at Mitra Medika Hospital. This research using qualitative research. To gather all of the important data the researchers using various techniques such as interview, observation, and documentation. The subjects of this study were 1 head of medical record, 1 medical record officer, and 5 poly nurses. The results of this study that there was still lack of knowledge and attitude, inadequate infrastructure or facilities. There was no motivation given by the head of the medical record, and the SOPs about the returning of outpatient medical record files had never been socialized. Things that can be taken are making an efforts to socialize SOPs to increase knowledge of health professionals, giving a warning from the head of medical records to nurses who are late returning medical record files, redesigning outpatient expedition books, providing work motivation and updated SOPs related to returning medical record files outpatient.